RASULULLAH SEBAGAI KONSELOR PROFFESIONAL - AHMAD PUTRA; PRASETIO RUMONDOR (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2019)
This paper explains about the figure of the Prophet who has unwittingly carried out a process of guidance and counseling to the people and followers. The process of guidance and counseling that we know in the current era, in fact the Prophet had practiced in the past when he lived and became a chosen human being. It's just that, now the counseling process is mostly done by counseling teachers in schools and applications from teachers or lecturers in front of many people. It seems we need to go back to see and read the history of the life of the Prophet in inviting people to goodness so that behind the struggle, a professional counseling process is drawn. It is intended that the generations of Islam and the Muslim world will understand that Rasulullah is a professional counselor and his life is filled with the practice of counseling itself. How he invites, gives advice, shows the right path and provides reinforcement to the people and their enemies into a form of counseling process that is actually not much different from the current counseling process.